(untitled) (Research, Society and Development, 2021)
This study aims to identify the factors that lead to the occurrence of penile trauma during penetration during sexual intercourse, and to understand the contributions of health professionals to patients with fractured penises. It is a descriptive study, with a qualitative approach, carried out between the months of May and December 2020, through the systematic review of articles indexed in the Platform of the Virtual Health Library (VHL). Inclusion criteria were full articles in Portuguese, English and Spanish. Published in full according to the proposed theme, and scientific articles published in the databases covering the years 2000 to 2020. As exclusion criteria, articles that were not relevant to the theme, duplicate, incomplete materials, abstracts, reviews, debates and materials unavailable in full. To collect the data, 10 scientific articles were analyzed. The results of the study describe that the fracture occurs when the erect penis leaves the vaginal cavity and when trying to penetrate again, the penis is bent abruptly and forced. Following the various contributions of health professionals to this incident. We conclude that penile trauma is considered a rare urological emergency, comprising a significant impact on the individual’s general point of view and sexual health, penile injury should be analyzed based on anamnesis, and on the individual’s physical examination, diagnostic methods by image must be requested in view of uncertainty and diagnostic accuracy.